2022
DOI: 10.1109/lra.2022.3192760
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Mechanical Properties of a Spherical Parallel Link Mechanism With Arc Prismatic Pairs

Abstract: A two-degrees-of-freedom spherical parallel link mechanism (2-DOF SPM) was designed to ensure that it only has rotational degrees of freedom in two directions around a fixed center. In general, 2-DOF SPM includes passive rotating pairs, and at least two actuators are needed to change the end-effector posture. The arrangement of the links and pairs determines the characteristics and performance of SPM, so 2-DOF SPMs were designed considering various requirements, such as output torque, accuracy, and space const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The spherical mechanism has rotational degrees of freedom in two directions around a fixed center. Saiki, N. et al [35] theoretically confirmed the influence that the arc sliders' friction had on the workspace of the mechanism proposed in [34] and used roller guides to reduce friction created by the arc sliders. The two-DOF curved biaxial swing spherical mechanism with two active arc sliders can be utilized in automobiles such as stabilization platforms and acceleration impact reduction mechanisms.…”
Section: State-of-the-art In Studying Spherical Mechanismsmentioning
confidence: 94%
“…The spherical mechanism has rotational degrees of freedom in two directions around a fixed center. Saiki, N. et al [35] theoretically confirmed the influence that the arc sliders' friction had on the workspace of the mechanism proposed in [34] and used roller guides to reduce friction created by the arc sliders. The two-DOF curved biaxial swing spherical mechanism with two active arc sliders can be utilized in automobiles such as stabilization platforms and acceleration impact reduction mechanisms.…”
Section: State-of-the-art In Studying Spherical Mechanismsmentioning
confidence: 94%
“…Similarly, spherical trigonometry was used for the inverse and forward kinematics analysis of an eye surgery robot with spherical architecture [65]. In addition, the application of spherical trigonometry for similar problems was shown in [22], [25], [30], [75], and [76]. reviewed in [9].…”
Section: ) Inverse Kinematicsmentioning
confidence: 99%